2016
DOI: 10.2337/db16-0051
|View full text |Cite
|
Sign up to set email alerts
|

CD40 in Retinal Müller Cells Induces P2X7-Dependent Cytokine Expression in Macrophages/Microglia in Diabetic Mice and Development of Early Experimental Diabetic Retinopathy

Abstract: Müller cells and macrophages/microglia are likely important for the development of diabetic retinopathy; however, the interplay between these cells in this disease is not well understood. An inflammatory process is linked to the onset of experimental diabetic retinopathy. CD40 deficiency impairs this process and prevents diabetic retinopathy. Using mice with CD40 expression restricted to Müller cells, we identified a mechanism by which Müller cells trigger proinflammatory cytokine expression in myeloid cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
192
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(199 citation statements)
references
References 47 publications
7
192
0
Order By: Relevance
“…Indeed, expression of CD40 restricted to Müller cells was sufficient to cause capillary degeneration in diabetic transgenic mice. 46 Long-term studies in diabetic P2X 7 −/− mice may help elucidate the in vivo role of this receptor in capillary degeneration. We recently observed that P2X 7 receptor also promotes expression of proinflammatory cytokines in the diabetic retina.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, expression of CD40 restricted to Müller cells was sufficient to cause capillary degeneration in diabetic transgenic mice. 46 Long-term studies in diabetic P2X 7 −/− mice may help elucidate the in vivo role of this receptor in capillary degeneration. We recently observed that P2X 7 receptor also promotes expression of proinflammatory cytokines in the diabetic retina.…”
Section: Discussionmentioning
confidence: 99%
“…We recently observed that P2X 7 receptor also promotes expression of proinflammatory cytokines in the diabetic retina. 46 Ligation of CD40 in human and mouse Müller cell lines caused secretion of ATP that in turn induced P2X 7 receptor–dependent IL-1β and TNF-α secretion by bystander myeloid cells. 46 Moreover, diabetic transgenic mice that expressed CD40 restricted to Müller cells exhibited retinal upregulation of IL-1β and TNF-α was dependent on P2X 7 receptor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…37 Overall, these findings are consistent with previous studies in other retinal diseases showing that Nrf2 influences the integrity of the BRB. 32 Increasing evidence indicates that DR is a pro-inflammatory condition, and IL-6 and TNF-a as well as the chemokine MCP-1 and the leukocyte adhesion molecule, ICAM-1 are implicated in the pathogenesis of DR. 30,[38][39][40] Müller cells are recognized as an important mediator and source of the increased levels of these pro-inflammatory factors in DR. 10,11,41 The ability of dh404 to reduce the increased production of IL-6, TNF-a, MCP-1, and ICAM-1 in the retina of diabetic rats as well as Müller cells exposed to hyperglycemia highlights the importance of Müller cells in DR and the powerful anti-inflammatory capacity of Nrf2 activation.…”
Section: Discussionmentioning
confidence: 99%